Investigating the mediating role of resilience in the relationship between early maladaptive schemas and existential anxiety in people with anxiety and depression - Marjan pourdehghan; Hamzeh Akbari; Kazem Shariatnia (مجله علوم روانشناختی)
Background: Several studies have emphasized the relationship between early maladaptive schemas and existential anxiety with psychological disorders such as anxiety and depression. On the other hand, resilience has been introduced as a mediating factor between mental health and many other variables. So far, no specific research has investigated the mediator role of resilience in the relationship between early maladaptive schemas and existential anxiety in people with anxiety and depression. Aims: The present study was conducted with the aim of investigating the mediator role of resilience in the relationship between early maladaptive schemas and existential anxiety in people with depression and anxiety. Methods: The current research was cross-sectional and its analysis was done by correlational method and structural equation modeling (SEM), specifically regression equations. The statistical population of this research included all the people who referred to counseling clinics and psychological services in the cities of Sari and Babol in the summer and fall of 2022. To determine the sample size, according to the number of observed variables and assigning a coefficient of 15 for each observed variable, 600 people were selected as the sample size, This number was selected as a statistical sample by purposeful sampling. To collect data, questionnaires of the Early Maladaptive Schema Questionnaire-Short Form (Yang, 1998), resilience (Conner-Davidson, 2003) and existential anxiety (Good & Good, 1974) were used. Structural equation modeling method and SPSS-22 and Amos-23 software were used for data analysis. Results: The findings of the present study showed that the proposed model has a good fit. Also, the findings showed that there is a direct relationship between the initial maladaptive schema and existential anxiety. Also, there is an indirect relationship between the initial maladaptive schema and existential anxiety with the mediation of resilience (P≥0.01). Conclusion: According to the results obtained, the mediating role of the resilience variable was confirmed in the present study, and considering the many tensions that people with anxiety and depression face, It is suggested that psychologists and counselors in the clinical and health fields strengthen this ability to deal with anxiety and depression in clients.